Peran Baznas Kampar Dalam Memberdayakan Ekonomi Masyarakat Di Desa Ridan Permai - Khairi, Rifqil; Winario, Mohd; Zakir, Muhammad; Amalia, Nala; Putri, Berliana (EL-EMIR Institute, 2025)
The purpose of this study is to determine the role of BAZNAS Kampar in empowering the economy of the community in Ridan Permai village. The target of the output of this study is that the results of the study can be utilized by the research site, for readers and this study is published in the national journal sinta 3 or sinta 4, dummy book, complete report results. The research site is at BAZNAS Kampar Regency, the population and sample of the study are all leaders and employees of BAZNAS Kampar Regency, sample determination by snowball sampling. Data analysis technique by qualitative descriptive analysis. The planned research budget is Rp. 10,550,000 consisting of honorarium, cost of consumables, data collection and reporting costs and research outputs. The results of this study are Through the spirit of